Estilos de apego y dependencia emocional en adolescentes - Guairacaja López, Jessica Alexandra (2025)
Emotional dependence is a pattern characterized by the search for security, validation, and affection, while attachment styles are patterns of behavior and interaction in interpersonal relationships. This study aims to analyze attachment styles and emotional dependence in adolescents through bibliographic and descriptive documentary research. It was made up of 481 scientific articles from the period 2014 to 2024 in Spanish and English, to which a non-probabilistic sampling was applied at the convenience of the authors, a sample of 19 scientific articles from different databases was selected, such as Web of Science, Google Scholar, Dialnet, Scopus, Scielo, Redalyc, and Pubmed, applying the Prisma 2020 Flow Diagram. Organizing them in bibliographic review sheets and critical review forms, the evaluation instrument for the Critical Analysis of Quantitative Research (CRF-QS) was used to collect data and evaluate the methodological quality of the selected articles. According to the results, the attachment style with the highest prevalence in adolescents is secure attachment, which fosters stable and positive relationships with caregivers; anxious, avoidant, and disorganized attachment are related to problems of aggressiveness, impulsivity, and lack of emotional closeness. In addition, a close relationship between attachment styles and emotional dependence was found, highlighting insecure, anxious, and fearful attachment as predictors in the appearance of dependent characteristics such as attention seeking and overprotection. On the contrary, the secure attachment presented at an early age with caregivers acts as a protective factor against dependence, positively impacting adolescents' emotional and behavioral wellbeing.